Prevalence of diabetes, hypertension, and the socio-demographic predictors of the type of facility utilized for related services in rural Telangana - Wassey, M. Abdul; Giri, Ashish; Raikwar, Aakash; Dogra, Vishal (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes mellitus and hypertension are chronic conditions that, on one hand demand early detection, screening, and treatment and on the other, require longitudinal follow-up for their successful management. Piramal Swasthya’s Arogyaseva program uses two contrasting methods (MMU and static clinic) to deliver diabetes and hypertension-related care. The MMU provides doorstep delivery of care, while the static clinic is located by the highway, is equipped with a telemedicine center, and has slightly higher diagnostic and therapeutic capabilities. The study aims to find the prevalence of diabetes and hypertension, and determine the association between the sociodemographic factors and the type of facility utilized for these conditions. Methods: This cross-sectional study is a secondary data analysis of the aggregated data of patients who availed health services at the Mobile Medical Unit and the static clinic. The data was analyzed to find out the prevalence of diabetes and hypertension, and Binary logistic regression was used to determine socio-demographic predictors of the type of health facility used for diabetes and hypertension-related care. Results: Overall hypertension and diabetes prevalence was 24% and 7%, respectively. Women (aOR 1.3; 95% CI 1.122–1.510), illiterate (aOR 2.61; 95% CI 2.021-3.392), hypertensives (aOR 3.28; 95% CI 2.807-3.846) and the elderly (aOR 1.43; 95% CI 1.204-1.721) were significantly more likely to utilize MMU based outreach facility compared to their respective baseline counterparts. Conclusions: The mobile medical unit can play a significant role in delivering hypertension and diabetes-related care, especially to women and the elderly.